A strength Pareto evolutionary algorithm–based conflict assessment framework of electricity market participants' objectives in generation maintenance scheduling. (30th December 2011) - Latify, Mohammad Amin; Seifi, Hossein; Mashhadi, Habib Rajabi
SUMMARY Conflicts between independent system operators (ISOs) and power producers, each preferring the annual maintenance plans based on their own objectives, have resulted from power system restructuring. Therefore, the ISO needs to specify how much the producers are free to adjust their maintenance programs on their own, without violating reliability criteria. In this article, a conflict assessment framework is described to characterize the degree of conflict among the electricity market participants' (ISO and producers) objectives. Four steps, namely, information gathering, mathematical modeling of the objectives, conflict front discovery, and finally the sensitivity analysis, were proposed as the basic steps of the framework. In this way, a multiobjective optimization problem was introduced by which a set of compromise solutions, denoted as a Pareto‐optimal front, can be found. To discover the front, the strength Pareto evolutionary algorithm was used as a robust evolutionary optimization technique. For the sensitivity analysis, two parameters, namely, the front curve relative change and its degree of linearity, were used. The proposed framework was tested on IEEE‐RTS, and its capabilities were assessed and appreciated. Copyright © 2011 John Wiley & Sons, Ltd.